Digital Transformation and Sustainable Outcomes: An Updated Systematic Literature Review (2020–2026) - Indra Suteja; Purwanto Purwanto; Felix Siswanto (Green Publisher Indonesia, 2026)
A systematic review following the PRISMA guidelines, this study analyzes Scopus-indexed papers published from 2020 to 2026 in order to shed light on how digital transformation enables sustainability-oriented outcomes and whether these contributions seem rooted in organizational change rather than represent aspirational disclosures of sustainability-related information. In the initial search phase, a total of 1,208 records were identified; after screening, retrieval and eligibility assessment of these studies from both electronic databases and hand-searching, just 78 studies were included in the final synthesis. Our findings show that digital transformation drives sustainability in six main avenues—namely ESG governance, eco-innovation, decarbonization, circular economy practices, digital maturity and social sustainability. However, with digital transformation being identified as sustainability by other means, without appropriate organizational capabilities and data governance that include adequate data and analytics support for innovation routines, regulatory pressures and strategic decision-making processes to be adopted together at scale across an organization because they are complementary. Also, the review suggests that by relying heavily on a style of quantitative testing based on looking for associations between concepts in datasets empirically available, research suffers from conceptual inconsistencies and uneven coverage across empirical contexts. The review presents a new conceptualization for digital transformation as an enabler of sustainability, which comes with execution conditions and identifies future research agendas to distinguish genuine sustainability effects from the simple prominence of sustainability.